The impact of COVID-19 on the international energy trade network centrality and community structures. Issue 8 (4th May 2023) - Cai, Hongbo; Huang, Siyu; Wu, Zongning
ABSTRACT: Global trade including energy trade is expected to suffer a significant contraction as a result of the COVID-19 pandemic. In this paper, we try to measure the impact of the COVID-19 pandemic on the national status and international energy trade patterns. We apply the networks theory to quantify the dynamic process of the international energy trade network in the year 2018–2020, deriving the Ω centrality to capture both national economic status and its topologic characteristics. Under the COVID-19, multilateral energy trade was blocked, thereby some resource-exporting countries show a downward rank of the Ω centrality, and the opposite situation is in higher levels of economic development. By using the community detection method, we also found that new small communities detached from communities that formed before the COVID-19, but geographical related patterns of international energy trade network communities were not affected by the COVID-19 pandemic.